Using Macrocyclic G‐Quadruplex Ligands to Decipher the Interactions Between Small Molecules and G‐Quadruplex DNA. Issue 65 (19th September 2022) - Andréasson, Måns; Bhuma, Naresh; Pemberton, Nils; Chorell, Erik
Abstract: This study aims to deepen the knowledge of the current state of rational G4‐ligand design through the design and synthesis of a novel set of compounds based on indoles, quinolines, and benzofurans and their comparisons with well‐known G4‐ligands. This resulted in novel synthetic methods and G4‐ligands that bind and stabilize G4 DNA with high selectivity. Furthermore, the study corroborates previous studies on the design of G4‐ligands and adds deeper explanations to why a) macrocycles offer advantages in terms of G4‐binding and ‐selectivity, b) molecular pre‐organization is of key importance in the development of strong novel binders, c) an electron‐deficient aromatic core is essential to engage in strong arene‐arene interactions with the G4‐surface, and d) aliphatic amines can strengthen interactions indirectly through changing the arene electrostatic nature of the compound. Finally, fundamental physicochemical properties of selected G4‐binders are evaluated, underscoring the complexity of aligning the properties required for efficient G4 binding and stabilization with feasible pharmacokinetic properties. Abstract : Binding : This study aims to add a deeper level of knowledge to the binding interactions between G4‐ligands and G4 DNA to advance the design of improved G4‐ligands. This is achieved by biophysical and physicochemical evaluations complemented by computational studies of both novel and well‐known G4‐ligands.